Efeitos da adição da estimulação elétrica nervosa transcutânea em um programa de exercícios terapêuticos em pacientes sedentários com cervicalgia crônica: ensaio clínico randomizado cego - SOUSA, Paulo Henrique Martins de (2021)
Overview: The conservative treatment is the most coherent clinical management with a view to proper rehabilitation of patients with chronic neck pain, with a trend towards the use of therapeutic exercise. However, uncertainties about the effectiveness of therapeutic exercises still persist, making it necessary to conduct further studies, especially with regard to the combination of therapeutic exercises with electrotherapy in the treatment of chronic cervical pain. Objective: To evaluate the clinical effects of adding high and low-frequency transcutaneous electrical stimulation (TENS) to a specific therapeutic exercise program for the treatment of patients with chronic neck pain. Methods: Sixty participants were randomized into three groups: therapeutic exercise group + placebo TENS (n = 20), therapeutic exercise group + high-frequency TENS (n = 20) and therapeutic exercise group + low-frequency TENS (n = 20). The following assessment instruments were used: Numerical Pain Rating Scale, Neck Disability Index, Pain-Related Catastrophizing Thoughts Scale, and Tampa Scale of Kinesiophobia. Results: The three groups were similar at baseline for personal and clinical characteristics, depending on the randomization performed. Regarding the main study analyses, there were no significant (p > 0.05) and clinical (d < 0.80) differences between the groups for the main variable (disability), nor for the secondary variables (pain, catastrophizing, and kinesiophobia). Conclusion: High or low-frequency TENS, compared to placebo TENS, does not generate additional clinical benefits to an exercise program for patients with chronic neck pain.